Model Zero-One Linear Programming untuk Penjadwalan Raw Mill dan Cement Mill - Wirdianto, Eri; Arnes, Ericho Chandra (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
The scheduling of electrical energy usage during Peak Load Period (PLP) is a complicated problem that has been faced by PT Semen Padang after Indonesian Power Company (PLN) implemented the demarcation regulation of electrical energy usage during PLP (6:00 – 10:00 p.m.) which may not exceed 44.100 kWH. This regulation forces Production Department of PT Semen Padang to arrange the “on (1) or off (0)” schedule for the Raw Mills and Cement Mills during PLP. A Raw Mill or Cement Mill can be switched-off if the specified criteria are satisfied. Those criteria refer to the achievement of daily production targets, silo content at PLP, and the requirement for particular Raw Mill or Cement Mill to be off during those 4 hours of PLP. Meanwhile, the constraints are related to the length of machining hours of Raw Mill, Kiln or Cement Mill before preventive maintenance takes place. To solve this problem, a scheduling model for Raw Mills and Cement Mills on-off during PLP is then developed using a linear programming approach. The decision variables are the “on-off” state of Raw Mills and Cement Mills during PLP, while the objective function is to minimize the penalty expense of energy used during PLP. The developed scheduling model has the ability to solve the problem of the “on-off” assignment for Raw Mills and Cement Mills from Indarung II to Indarung V. This scheduling model can decrease the penalty of electrical energy expense during PLP from Rp. 3.07 billion to Rp. 1.79 billion.